Regulation of gingival epithelial cytokine response by bacterial cyclic dinucleotides - Samira Elmanfi; Jie Zhou; Herman O. Sintim; Eija Könönen; Mervi Gürsoy; Ulvi Kahraman Gürsoy (Taylor&Francis, 2022)
Background: Cyclic dinucleotides (cyclic di-guanosine monophosphate (c-di-GMP) and cyclic di-adenosine monophosphate (c-di-AMP)) and lipopolysaccharides (LPS) are pathogen-associated molecular patterns (PAMPs). Individual impacts of PAMPs on immune system have been evaluated, but simultaneous actions of multiple PAMPs have not been studied.
Objective: Examination the effects of cyclic dinucleotides and Porphyromonas gingivalis LPS on gingival epithelial cytokine response.
Methods: Human gingival keratinocytes (HMK) were incubated with 1, 10, and 100 µM concentrations of c-di-GMP and c-di-AMP, either in the presence or absence of P. gingivalis LPS. Intra- and extracellular levels of interleukin (IL)-1β, IL-8, IL-1Ra, monocyte chemoattractant protein (MCP)-1, and vascular endothelial growth factor (VEGF), were measured using the Luminex technique.
Results: LPS decreased extracellular IL-8 levels, while the presence of c-di-AMP inhibited this effect. Incubating HMK cells with c-di-AMP (alone or with LPS) elevated the extracellular level of MCP-1. Extracellular VEGF level increased when cells were incubated with LPS and c-di-GMP together, or with c-di-AMP alone. LPS and c-di-AMP suppressed intracellular IL-1β levels. The c-di-AMP elevated intracellular levels of IL-1Ra.
Conclusion: c-di-AMP and, to a lesser extent, c-di-GMP regulate keratinocyte cytokine response, either as an aggregator or as a suppressor of LPS, depending on the cytokine type.